The Effect of Relaxation Music Therapy in Overcoming Depressive Disorders in Adolescents in Purwakarta Regency, Indonesia - Roslinawati, Roslinawati (HM Publisher, 2024)
Depression is a mental disorder that is often experienced by teenagers. Relaxation music therapy is one method that can be used to treat depressive disorders. This study aims to determine the effect of relaxation music therapy in treating depressive disorders in adolescents in Purwakarta Regency, Indonesia. This research uses a quasi-experimental method with a pretest-posttest control group design. The research sample was teenagers aged 15-19 years who experienced depressive disorders in Purwakarta Regency, Indonesia. The sample was divided into two groups, namely the experimental group which was given relaxation music therapy and the control group which was not given relaxation music therapy. The results showed that there was a significant difference between the experimental group and the control group in terms of depression scores after being given relaxation music therapy. Depression scores in the experimental group decreased more significantly compared to the control group. Based on the results of this research, it can be concluded that relaxation music therapy can be an effective method in treating depressive disorders in adolescents.